Pre-procedural assessment of aortic annulus dimensions for transcatheter aortic valve replacement: comparison of a non-contrast 3D MRA protocol with contrast-enhanced cardiac dual-source CT angiography. (27th July 2015) - Ruile, Philipp; Blanke, Philipp; Krauss, Tobias; Dorfs, Stephan; Jung, Bernd; Jander, Nikolaus; Leipsic, Jonathon; Langer, Mathias; Neumann, Franz-Josef; Pache, Gregor
Abstract: Aims: To evaluate the feasibility of a non-contrast three-dimensional (3D)-FLASH magnetic resonance angiography (MRA) protocol for pre-procedural aortic annulus assessment for transcatheter aortic valve replacement (TAVR) in comparison with cardiac dual-source computed tomography angiography (CTA). Methods and results: In this prospective study, 69 of 104 consecutive patients (mean age 81.8 ± 5.4 years, 37.7% arrhythmic) with severe aortic stenosis who had undergone pre-TAVR cardiac CTA received a respiratory and ECG-triggered, non-contrast 3D-FLASH MRA at 3 T. Annular area measurements were obtained at mid-diastole for both modalities whereas maximum systolic area was assessed by CTA only. Systolic MRA dimensions were modelled, by adding the relative difference of systolic and diastolic CTA area dimensions as a corrective factor. Hypothetical prosthesis sizing was performed based on systolic CTA, diastolic, and modelled systolic MRA area measurements. MR image quality and degree of annular calcifications were evaluated using 4-point-grading scales. The mean acquisition time was 14 ± 4.2 min. The mean image quality was 3.1 ± 0.9 with only two examinations rated non-diagnostic. The mean degree of calcifications was equal. As assessed by Bland–Altman analysis, there was no relevant systematic difference between area measurements for modelled systolic MRA and systolic CTA [the mean difference −3.1 mm 2 (limits of agreement −44.4 mm 2 ; 38.2 mm 2 )]. Agreement for hypothetical prosthesis sizing was found in 63 of 67 (94%) patients for systolic CTA and modelled systolic MRA. Conclusion: The employed non-contrast 3D-FLASH MRA protocol allows for reliable assessment of aortic annulus dimensions and calcifications even in the presence of arrhythmias in an all-comers pre-TAVR population. Implementation of this technique appears legitimate in patients at an increased risk for contrast-induced nephropathy.